Pengaruh Literasi Lingkungan Terhadap Environmental Responsibility Siswa Kelas XI SMA Negeri 2 Bandar Lampung - Andi Yudha Pratama; Rini Rita T. Marpaung; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2020)
This study aims to determine the effect of the Adiwiyata program on environmental literacy and environmental care attitudes. The research design used was post facto design. The sampling technique is random sampling. The sample used was 58 students taken from 20% of the total student population in SMA Negeri 2 Bandar Lampung. Research data obtained from test questions and questionnaires, then analyzed using the independent sample t-test. The results showed an environmental literacy value of 72.0. The results of students' environmental care attitudes about aspects of trust, perception and knowledge of the environment amounted to 73.0. The results of students' environmental care attitudes aspects of individual feelings towards the object of attitudes concerning emotional problems with the environment by 70.0. The results of students' environmental care attitudes aspects of the tendency to act or behave towards the environment of 81.0. Hypothesis test results indicate that there is an influence of the Adiwiyata program on environmental literacy as evidenced by the Sig0,000 ≤ 0.05 value.Penelitian ini bertujuan untuk mengetahui pengaruh program Adiwiyata terhadap literasi lingkungan dan sikap peduli lingkungan. Desain penelitian yang digunakan adalah desain expost facto. Teknik pengambilan sampel yaitu random sampling. Sampel yang di gunakan berjumlah 58 siswa yang diambil dari 20% jumlah populasi siswa/i di SMA Negeri 2 Bandar lampung. Data penelitian diperoleh dari soal tes dan kuisioner, kemudian dianalisis menggunakan uji independent sampel t-Test. Hasil penelitian menunjukkan nilai literasi lingkungan sebesar 72,0. Hasil sikap peduli lingkungan siswa aspek kepercayaan, persepsi dan pengetahuan tentang lingkungan sebesar 73,0. Hasil sikap peduli lingkungan siswa aspek kecenderungan untuk bertindak atau berprilaku terhadap lingkungan sebesar 81,0. Hasil uji hipotesis menunjukkan terdapat pengaruh program Adiwiyata terhadap literasi lingkungan dibuktikan dengan nilai Sig0,000 0,05.Kata kunci: Adiwiyata, literasi lingkungan, sikap peduli lingkunganhttp://dx.doi.org/10.23960/jbt.v8.i1.01